(untitled) (Indian Journal of Public Health Research & Development, 2026)
Inspite of various guidelines for snakebite management, in real life, every case of snakebite poses a unique challenge and one may not always be able to abide strictly by the guidelines. There are a just a handful of physicians who are experts in managing snakebite. This article has been written by Dr D C Patel in Dharampur, Gujarat who has been treating snakebite victims for more than 30 years. This short communication draws on over three decades of clinical data and practice-based insights, offering guidance for public health professionals and community medicine practitioners in remote, resource-constrained settings. Data from April 1993 to March 2024 has been presented along with tips on snakebite management. His analysis presents a few insights- Russell’s viper bites have increased steeply over the years in Dharampur area and Valsad district of Gujarat. The mean number of vials used to manage bites by various species have fallen over time. Regular public awareness programshave borne fruit. Fewer patients visit faith healers and they reach the hospital quickly. Management of cases using the syndromic approach, early and adequate administration of clinically estimated amount of AVS along with organ support is the essential triad of management.